The Covert Life of Hospital Architecture - Zook, Julie; Sailer, Kerstin (UCL Press, 2022)
The Covert Life of Hospital Architecture addresses hospital architecture as a set of interlocked, overlapping spatial and social conditions. It identifies ways that planned-for and latent functions of hospital spaces work jointly to produce desired outcomes such as greater patient safety, increased scope for care provider communication and more intelligible corridors. By advancing space syntax theory and methods, the volume brings together emerging research on hospital environments. Opening with a description of hospital architecture that emphasizes everyday relations, the sequence of chapters takes an unusually comprehensive view that pairs spaces and occupants in hospitals: the patient room and its intervisibility with adjacent spaces, care teams and on-ward support for, and the intelligibility of public circulation spaces for visitors. The final chapter moves outside the hospital to describe the current healthcare crisis of the global pandemic as it reveals how healthcare institutions must evolve to be adaptable in entirely new ways. Reflective essays by practicing designers follow each chapter, bringing perspectives from professional practice into the discussion. The Covert Life of Hospital Architecture makes the case that latent dimensions of space as experienced have a surprisingly strong link to measurable outcomes, providing new insights into how to better design hospitals through principles that have been tested empirically. It will become a reference for healthcare planners, designers, architects and administrators, as well as for readers from sociology, psychology and other areas of the social sciences.